Peran Mahasiswa Magang dalam Mendukung Transparansi Administrasi dan Penyaluran Dana di BAZNAS Kota Payakumbuh - Meri Gustiara (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research is motivated by the importance of transparency and accountability in the management of zakat funds at BAZNAS Payakumbuh City, which is essential for strengthening public trust and optimizing the utilization of zakat. The study aims to analyze the role of internship students in supporting administrative transparency and the effectiveness of zakat fund distribution. A descriptive qualitative method was employed through participatory observation, unstructured interviews, and document analysis, allowing the researcher to directly examine administrative processes in the field. The findings show that internship students make significant contributions to improving data accuracy, verifying transfer receipts, organizing documents, and assisting in the distribution of aid to beneficiaries. Their involvement accelerates administrative workflows, enhances the quality of reporting through the SiMBA system, and strengthens institutional accountability. The study concludes that internship students function as an additional human resource capacity that improves transparency, operational efficiency, and public trust in BAZNAS. Strengthening collaboration with academic institutions is recommended to support more professional and accountable zakat governance.